2008
DOI: 10.3922/j.psns.2008.1.013
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the dopaminergic system to the effect of chronic fluoxetine in the rat forced swim test.

Abstract: Chronic administration of selective serotonin reuptake inhibitors (SSRI) enhances dopaminergic activity. However, the role of enhanced dopaminergic transmission in the therapeutic effects of this kind of antidepressants is still unclear. Drugs producing dopaminergic activation lead to an increment in general activity. Thus, it is reasonable to assume that some of the therapeutic effects of SSRIs are due to dopaminergic enhanced functionality. The forced swim test (FST) is a widely used test in the screening of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Rats with PD showed depressive-like behavior, as evidenced by increased immobility time of swimming test, when compared with normal animals. In fact, depression associates dopaminergic system dysfunction [29] that was indicated in the present study by the presence of negative correlation between striatal dopamine and immobility time of swimming test. An antidepressive effect was exerted by piracetam or vincamine, which is probably due to their neuroprotective effect, as evidenced by improvement in GDNF and increasing dopamine level in the striatal tissue.…”
Section: Discussionsupporting
confidence: 68%
“…Rats with PD showed depressive-like behavior, as evidenced by increased immobility time of swimming test, when compared with normal animals. In fact, depression associates dopaminergic system dysfunction [29] that was indicated in the present study by the presence of negative correlation between striatal dopamine and immobility time of swimming test. An antidepressive effect was exerted by piracetam or vincamine, which is probably due to their neuroprotective effect, as evidenced by improvement in GDNF and increasing dopamine level in the striatal tissue.…”
Section: Discussionsupporting
confidence: 68%
“…Laura A Leon suggested that for the sake of precision in animal modeling, animal models like active avoidance, social isolation, learned helplessness, behavioral despair, genetic depression models would be important to evaluate the antidepressant activity of a new potential compound. 18 Social isolation stress is a valuable stress paradigm for investigating the effects of chronic psychosocial stress on various pathophysiological alterations in animals. 19 Therefore, we conducted this study that compared the effects of imipramine, a tricyclic antidepressant and nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…It suggests that SRT generates an anxiolytic effect during the light period [97]. In line with these findings, acute treatment with antidepressants also could increase locomotor activity [98] and reduce the immobility time in rats [99]. Some prior studies also demonstrated hyperactivity in mice with reducing immobility time and an increase in escape behavior after treatment with serotonergic and noradrenergic antidepressants [100,101].…”
Section: Several Antidepressants Induced a Hyperactive Response In Zebrafish Larval Locomotor Activitymentioning
confidence: 80%